Levofloxacin loaded poly (ethylene oxide)-chitosan/quercetin loaded poly (D,L-lactide-co-glycolide) core-shell electrospun nanofibers for burn wound healing - Monavari, Mahshid; Sohrabi, Razieh; Motasadizadeh, Hamidreza; Monavari, Mehran; Fatahi, Yousef; Ejarestaghi, Negin Mousavi; Fuentes-Chandia, Miguel; Leal-Egaña, Aldo; Akrami, Mohammad; Homaeigohar, Shahin (Frontiers in Bioengineering and Biotechnology, 2024)
This study developed a new burn wound dressing based on core-shell nanofibers that codeliver antibiotic and antioxidant drugs. For this purpose, poly(ethylene oxide) (PEO)-chitosan (CS)/poly(D,L-lactide-co-glycolide) (PLGA) core-shell nanofibers were fabricated through co-axial electrospinning technique. Antibiotic Levofloxacin (LEV) and antioxidant quercetin (QS) were incorporated into the core and shell parts of PEO-CS/PLGA nanofibers, respectively. The drugs could bond to the polymer chains through hydrogen bonding, leading to their steady release for 168 h. An in vitro drug release study showed a burst effect followed by sustained release of LEV and QS from the nanofibers due to Fickian diffusion. The NIH 3T3 fibroblast cell viability of the drug loaded coreshell nanofibers was comparable to that in control (tissue culture polystyrene (TCPS)), implying biocompatibility of the nanofibers and their cell supportive role. However, there was no significant difference in cell viability between the drug loaded and drug free core-shell nanofibers. According to in vivo experiments, PEO-CS-LEV/PLGA-QS core-shell nanofibers could accelerate the healing process of a burn wound compared to sterile gauze. Thanks to the synergistic therapeutic effect of LEV and QS, a significantly higher wound closure rate was recorded for the drug loaded core-shell nanofibrous dressings than the drug free nanofibers and control. Conclusively, PEO-CS-LEV/PLGA-QS core-shell nanofibers were shown to be a promising wound healing material that could drive the healing cascade through local co-delivery of LEV and QS to burn wounds.